2012
DOI: 10.1111/tpj.12054
|View full text |Cite
|
Sign up to set email alerts
|

The holocentric species Luzula elegans shows interplay between centromere and large‐scale genome organization

Abstract: SUMMARYIn higher plants, the large-scale structure of monocentric chromosomes consists of distinguishable eu-and heterochromatic regions, the proportions and organization of which depend on a species' genome size. To determine whether the same interplay is maintained for holocentric chromosomes, we investigated the distribution of repetitive sequences and epigenetic marks in the woodrush Luzula elegans (3.81 Gbp/1C). Sixtyone per cent of the L. elegans genome is characterized by highly repetitive DNA, with ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 67 publications
4
98
0
1
Order By: Relevance
“…Therefore, we applied antibodies against typical euchromatin-and heterochromatin-associated histone methylation marks (H3K4me3 and H3K9me2, respectively). In agreement with other holocentric species (15,27) the euchromatin and heterochromatic domains in R. pubera were found dispersed along the entire chromosomes (SI Appendix, Fig. S1 C and D).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, we applied antibodies against typical euchromatin-and heterochromatin-associated histone methylation marks (H3K4me3 and H3K9me2, respectively). In agreement with other holocentric species (15,27) the euchromatin and heterochromatic domains in R. pubera were found dispersed along the entire chromosomes (SI Appendix, Fig. S1 C and D).…”
Section: Resultssupporting
confidence: 89%
“…far for any species possessing holocentric chromosomes (14)(15)(16)(17). For instance, Heckmann, et al (15) have characterized the high-copy fraction of the Luzula elegans genome in detail, and none of the identified repeats showed colocalization with the holokinetic centromere.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The observed absence of positive selection on CenH3 in Luzula is in accordance with a recent finding in Luzula elegans which lacks centromeric repeats that would co-localize with kinetochore formation along an entire chromosome (Heckmann et al, 2013). In contrast, Marques et al (2015) have found a centromeric satellite repeat Tyba co-localized with kinetochore formation in holokinetic Rhynchospora pubera (Cyperaceae).…”
Section: Discussionsupporting
confidence: 77%
“…Henikoff et al, 2001;Talbert et al, 2004;Hirsch et al, 2009;Schueler et al, 2010) or on Caenorhabditis (Zedek and Bures, 2012) which is holokinetic in mitosis but forms a cup-like kinetochore in meiosis with ambiguous utilization of CenH3 (Chan et al, 2004;Monen et al, 2005). If the recurrent adaptive evolution of CenH3 is really a consequence of centromere drive, it should be missing (or at least less frequent) not only in lineages with symmetric meiosis but also in lineages with asymmetric meiosis that possess holokinetic chromosomes, such as the plant genus Luzula (Heckmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%